Survival outcomes of cytoreductive surgery and hyperthermic intraperitoneal chemotherapy in selected patients with stage IV gastric adenocarcinoma – A Canadian case series - Bénard, Florence; Marcil, Stéphanie; Mack, Lloyd; Deban, Melina; Bildersheim, Michael; Bouchard-Fortier, Antoine; Osman, Yasmin; Mercier, Frédéric; Purich, Kieran; Haase, Erika; Schiller, Dan; Soucisse, Mikael; et al. (European journal of surgical oncology, 2025)
Despite advances in systemic therapy, metastatic gastric cancer is associated with a poor prognosis. As peritoneal disease is common, several studies looked at the potential benefits of hyperthermic intraperitoneal chemotherapy (HIPEC) in this context, with encouraging results. However, no Canadian data currently exists on the subject. This study aims to report characteristics and outcomes of Canadian patients who underwent cytoreductive surgery and HIPEC (CRS-HIPEC) for gastric cancer associated with peritoneal disease or positive peritoneal cytology. This multicenter retrospective study included patients 18 years or older with gastric cancer associated with isolated peritoneal involvement who underwent CRS-HIPEC in five tertiary centers from 2016 to 2022. CRS-HIPEC was performed on 20 patients aged 34–69 years old, most of whom presented with poorly differentiated (90 %) adenocarcinoma, with synchronous peritoneal disease (95 %). Median PCI was 3 (0–13). The associated 90-day morbidity rate, defined as Clavien-Dindo grade III and above complications, was 10 %. At a mean follow-up of 23.3 months (range 4–48), 25 % of patients remained disease-free, with an estimated median overall survival of 24.2 months. CRS-HIPEC for gastric cancer can achieve longer term survival in highly selected patients with low-burden peritoneal disease or positive cytology. Ongoing randomized trials will further clarify patients’ selection criteria and benefits of this approach.